EXPLORATORY STUDY OF HUMAN RESOURCE BASED CONTROL MECHANISMS IN FINNISH-CHINESE INTERNATIONAL JOINT VENTURE: A FOREIGN PARENT PERSPECTIVE - Wazir, Sohail (My University, 2010)
The main objective of this case study is to explore the use of four human resource based control mechanisms: staffing of the key positions , training and development , performance appraisals and compensation and rewards in a Finnish-Chinese international joint venture from the foreign (Finnish) parent perspective . The study suggests that these four human resource strategies which have proven effective in various other organizational environments can be utilized as important control tools within the context of IJVs though their importance have been neglected in the past . The study also comes with three main findings. First the ranking of these control mechanisms based on their importance differed and the staffing of personnel at key positions gave a greater sense of control to the foreign parent over the IJV followed by training and development, compensation and rewards and performance appraisal. Secondly the foreign parent staffed the key positions only with the PCNs (parent company nationals) and no TCNs (third country nationals) or HCNs (host country nationals) were used. Third the exercise of these four human control mechanisms resulted in greater foreign parent satisfaction and IJV performance. The exercise of these control mechanisms by the foreign parent is explained in the light of agency theory. Effective employment of these mechanisms by the foreign parent firm and implications of these concepts for the mangers and others interested in the successful formation and management of IJVs are also presented. Data collection took place through six face to face interviews
Keywords: IJV Control; Human Resource Control Mechanisms; IJVs .; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|